2018
DOI: 10.1021/acs.energyfuels.8b02816
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Gas Hydrates Cold Flow Technology

Abstract: Gas hydrates cold flow can be defined as flow of non-adhesive and non-cohesive hydrate particles dispersed in the production fluids flowlines. Implementation of cold flow related hydrate management strategies might significantly reduce the costs of oil and gas field development and production by removing or reducing the need for injection of chemicals, insulation, and heating. Several research groups have performed experiments focusing on different methods of producing hydrate dispersion. Hydrate particles can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Natural gas hydrates (NGHs) are crystalline compounds composed of water and hydrocarbon gas molecules . NGHs are readily formed under the low-temperature and high-pressure conditions in oil and gas industry and could therefore pose a great threat to subsea flow assurance by agglomerating, jamming, bedding, and depositing in the transmission pipelines. So far, NGHs in subsea flow assurance have been extensively investigated, and several hydrate prevention/management strategies have been proposed. Except for NGHs, another big concern in subsea flow assurance is about wax. When the pipeline operating temperature falls below the wax appearance temperature (WAT), wax molecules dissolved in the crude oil will gradually precipitate and may deposit on the pipe wall, which may further lead to pipeline plugging.…”
Section: Introductionmentioning
confidence: 99%
“…Natural gas hydrates (NGHs) are crystalline compounds composed of water and hydrocarbon gas molecules . NGHs are readily formed under the low-temperature and high-pressure conditions in oil and gas industry and could therefore pose a great threat to subsea flow assurance by agglomerating, jamming, bedding, and depositing in the transmission pipelines. So far, NGHs in subsea flow assurance have been extensively investigated, and several hydrate prevention/management strategies have been proposed. Except for NGHs, another big concern in subsea flow assurance is about wax. When the pipeline operating temperature falls below the wax appearance temperature (WAT), wax molecules dissolved in the crude oil will gradually precipitate and may deposit on the pipe wall, which may further lead to pipeline plugging.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium distributions must satisfy conditions (8) and is advected by fluid, which can be given by the follow equation:…”
Section: Lbm Implementationmentioning
confidence: 99%
“…Applications of slicing (or cutting) droplets are mainly found in microfluidics [7] and also-on a larger scale-in static mixers. [8] Forte et al [9] investigated the fundamental mechanisms of oil droplet breakup in static mixers. They found that the drop size decreased to a critical point when the continuous phase (water) flow rate is increasing.…”
Section: Introductionmentioning
confidence: 99%
“…Although 100% conversion of water does not influence the particle size noticeably (which grows at a ratio of 1.09 wh   for methane hydrates), agglomeration can drastically change the number and average size of particles. Agglomeration is neglected for the sake of simplification (cold flow assumption; Straume et al, 2019), but coupling with proper population balance models (Balakin et al, 2010;Herri et al, 1999;Sampaio et al, 2017) will be done in a near future.…”
Section: Mathematical Modelmentioning
confidence: 99%